Elongated magnetic nanoparticles with high-aspect ratio: a nuclear relaxation and specific absorption rate investigation. Issue 34 (19th August 2019) - Avolio, Matteo; Gavilán, Helena; Mazario, Eva; Brero, Francesca; Arosio, Paolo; Lascialfari, Alessandro; Puerto Morales, M.
Abstract : High aspect-ratio elongated nanoparticles with suitable porosity present partially controlled chemico-physical properties to obtain good heating/contrast efficiency for biomedical applications. Abstract : Medical application of nanotechnology implies the development of nanomaterials capable of being functional in different biological environments. In this sense, elongated nanoparticles (e-MNPs) with high-aspect ratio have demonstrated more effective particle cellular internalization, which is favoured by the increased surface area. This paper makes use of an environmentally friendly hydrothermal method to produce magnetic iron oxide e-MNPs, starting from goethite precursors. At high temperatures ( T d ) goethite transforms into hematite, which subsequently reduces to magnetite when exposed to a hydrogen atmosphere for a certain time. It is shown that by adjusting T d it is possible to obtain Fe3 O4 e-MNPs with partially controlled specific surface area and magnetic properties, attributed to different porosity of the samples. The particles' efficiencies for diagnostic and therapeutic purposes (in magnetic resonance imaging and magnetic fluid hyperthermia, respectively) are very good in terms of clinical standards, some samples showing transversal proton nuclear relaxivity r 2 ( B 0 = 1.33 T) = 340 s −1 mM −1 and specific absorption rate SAR > 370 W g −1 at high field amplitudes ( B 0 = 55 mT). Direct correlations between the SAR, relaxivity, magnetic properties and porosity of the samples are found, and the physico-chemical processes underneath these correlations are investigated. Our results open the possibility of using very efficient high-aspect ratio elongated nanoparticles with optimized chemico-physical properties for biomedical applications.